The Black Sensible: escape routes for performances - Gadelha, José Juliano (Revista Brasileira de Estudos da Presença, 2022)
The article forges the principle of escape to think of the poetics of the body disappearance that encounter, in what the author calls fugitive performance, a way of making alive the modes of existence, which would be destined, by the reproductive futurism of the esthetical norm, to disappear and, consequently, to die. In a dialogue with Black Studies, anti-colonial criticism and my own thought on the sensitive field, the article traces the threads that expose the programs of re-theorization, representation, abstraction and performance underlying the traffic of the becoming-black in the arts.